2021
DOI: 10.1002/admi.202100962
|View full text |Cite
|
Sign up to set email alerts
|

Super‐Wetting Porous g‐C3N4 Nanosheets Coated PVDF Membrane for Emulsified Oil/Water Separation and Aqueous Organic Pollutant Elimination

Abstract: Super‐wetting multifunctional membranes are highly attractive in the current decade in the environmental remediation of wastewater containing water‐insoluble emulsified oils and water‐soluble hazardous organic pollutants. Herein, hydroxyl modified porous g‐C3N4 nanosheets (CNNS) coated polyvinylidene fluoride (PVDF) membrane is fabricated by a facile vacuum pumping process. Hydroxyl modified porous g‐C3N4 nanosheets are firmly immobilized on flexible PVDF substrate via sodium alginate (SA) adhesive to create a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…Relating the correlated differential volume to the differential height of the oil in the capillary tube may be expressed in Equation (6),…”
Section: Visualization Experiments and Theoretical Approachmentioning
confidence: 99%
See 1 more Smart Citation
“…Relating the correlated differential volume to the differential height of the oil in the capillary tube may be expressed in Equation (6),…”
Section: Visualization Experiments and Theoretical Approachmentioning
confidence: 99%
“…Previous studies have shown that there are many outstanding candidates for oil spill absorption materials. Many effective oil absorbent materials include sawdust, [3] membranes, [4,5,6] meshes, [7,8,9] and polymeric absorbents. [10,11] However, the limited absorption capacity and poor recyclability of these materials limit their industrial applicability.…”
Section: Introductionmentioning
confidence: 99%